Addition of Benzyl Amino Purine (BAP) to Induction of Drendan Seeds Buds (Lansium domesticum var. aqueum (Jack) Miq.) by In Vitro - Mayta Novaliza Isda; Febby Ika Desyana (Universitas Andalas, 2020)
Drendan (Lansium domesticum var. aqueum (Jack) Miq. is one of Indonesia's native tropical fruits. Drendan has high antioxidant activity and contains high nutrients, but has started to rarely be found in the field because its management and cultivation is rarely done due to its sour taste in vitro culture is a method or technique of plant propagation which can be an alternative to obtaining drendan seedlings in large quantities and in a short time vegetatively. The purpose of this study was to determine the effect of BAP on shoot induction from drendan seed explants and determine the best concentration of BAP on shoot growth of drendan seed explants in vitro. This study used a completely randomized design with BAP concentrations of 0, 1, 3, 5 and 7 mg / L BAP. The result of this research is the addition of BAP has been able to increase the percentage of live explants and the percentage of shoot formation. Giving BAP did not significantly affect the number of shoots and had a significant effect on shoot emergence time and shoot length. The addition of BAP resulted in slower shoot emergence time. Giving BAP was not able to stimulate shoot induction, but the addition of BAP could increase shoot length growth at a concentration of 5 mg / L BAP of 0.52 cm.